2020
DOI: 10.1097/j.pain.0000000000002034
|View full text |Cite
|
Sign up to set email alerts
|

Sex- and cell-dependent contribution of peripheral high mobility group box 1 and TLR4 in arthritis-induced pain

Abstract: Supplemental Digital Content is Available in the Text. Peripheral high mobility group box 1 promotes joint pain through TLR4 activation in immune cells that is strongly evident in male but not female mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 57 publications
3
21
1
Order By: Relevance
“…The same study has shown the involvement of TLR9 in the paclitaxel-induced release of TNF and CXCL1 from male, but not female, macrophages [ 96 ]. Similar sex dimorphisms have also been described in the role of TLR4 in pain processing [ 80 , 97 ]. Collectively, activation of RAGE and CXCR4 possibly by macrophage-derived at-HMGB1 may play a major part in CIPN due to paclitaxel.…”
Section: Role Of Hmgb1 In Cipnsupporting
confidence: 67%
See 2 more Smart Citations
“…The same study has shown the involvement of TLR9 in the paclitaxel-induced release of TNF and CXCL1 from male, but not female, macrophages [ 96 ]. Similar sex dimorphisms have also been described in the role of TLR4 in pain processing [ 80 , 97 ]. Collectively, activation of RAGE and CXCR4 possibly by macrophage-derived at-HMGB1 may play a major part in CIPN due to paclitaxel.…”
Section: Role Of Hmgb1 In Cipnsupporting
confidence: 67%
“…TLRs recognize pathogen-associated molecular pattern (PAMP) and DAMP molecules, followed by activation of the MyD88-dependent NF-κB pathway for production of pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α) and the MyD88-independent IRF pathway for production of interferon [ 12 , 77 ]. Extracellular HMGB1 interacts with membrane receptors including TLR2, a receptor for lipopeptide, TLR4, a receptor for LPS, and TLR5, a receptor for flagellin, leading to the development or aggravation of inflammatory and pain signals ( Figure 1 C) [ 16 , 78 , 79 , 80 ]. HMGB1 binding to nucleic acids penetrates into the cells, and stimulates endosomal TLR9, which is responsible for innate immunity and autoimmunity [ 12 , 15 , 81 , 82 ].…”
Section: Molecular and Biological Characteristics Of Hmgb1mentioning
confidence: 99%
See 1 more Smart Citation
“…This remains an integral process of not only pain induction as a protective mechanism, but also a transition to maladaptive chronic pain in some instances (Renthal et al, 2020 ). Discovering the sex-dependent roles of macrophages in tissue injury is paramount as the incidence macrophage-dependent chronic pain in females is lower than in males (Wiesenfeld-Hallin, 2005 ; Agalave et al, 2020 ; Rudjito et al, 2020 ). As such, identifying sex differences in macrophage biology will serve as a foundation for future studies aimed at exploiting immunological regulation in pain and will serve to create a more tailored approach to therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, we used the collagen antibody-induced arthritis (CAIA) model in which mechanical hypersensitivity was previously observed prior to, during, and following the antibody-induced flare of joint inflammation [20][21][22][23][24][25]. Interestingly, signs of bone loss remain several weeks after resolution of inflammation [20], raising the question whether bone erosion contribute to the persistency of hypersensitivity in this model.…”
Section: Introductionmentioning
confidence: 99%